Transcritical organic Rankine vapor compression refrigeration system for intercity bus air-conditioning using engine exhaust heat. (15th March 2015) - Yılmaz, Alper
Abstract: T-ORVC (Transcritical organic Rankine vapor compression) refrigeration system for intercity bus air-conditioning using engine exhaust heat is investigated. Wet refrigerant R134a and dry refrigerant R245fa are considered as refrigerants. Typical efficiencies for pump, turbine and compressor utilized in literature (namely LV (low values), MV (medium values) and HV (high values)) are compared for the influence on COP (coefficient of performance) of the system analyzed. The results are strongly dependent upon the efficiencies. COPH (coefficient of performance for heat energy) used for the heating of the refrigerant, coefficient of performance for electrical energy (COPW) needed for the pump and coefficient of performance for both heat energy and electrical energy (COPT) needed together for the heating of the refrigerant and for the pump (COPT) are calculated. Besides the isentropic efficiencies, mechanical, electromotor and electric energy production efficiencies are also taken into account. Using MV efficiencies, COPT values at 8 MPa pressure can be as high as 0.54 and 0.66 at 180 and 200 °C temperatures for R134a and R245fa, respectively. COPW values are very high and therefore electrical energy need is very low as compared to exhaust heat energy need. Assuming 30 kW of cooling load for an intercity bus and under different engine loads, all heat exchanger properties are determined. The results for a cooling load of 30 kW show that using T-ORVC (organic Rankine vapor compression cycle) system, air-conditioning of the intercity buses can be realized using waste heat energy of engine exhaust gases. Highlights: Modelling of transcritical organic Rankine vapor compression refrigeration system. Presentation of coefficient of performance depending on pressure and temperature. Determination of optimum pressures and temperatures for the refrigerants used. Analysis of all the heat exchangers used in the system. T-ORVC system is able to cover the total cooling load for air-conditioning of an intercity bus.